Numerical validation of viewfactor and FVDOM radiation models of openfoam ® and application in the study of food furnaces - Verdério Júnior, Sílvio Aparecido; Scalon, Vicente Luiz [UNESP]; Avallone, Elson; Mioralli, Paulo César (My University, 2018)
Continuous tunnel furnace has greater flexibility in heating and high productivity and it was becoming the best option for processing industrialized food products. The main objective of this work is the validation of the results from radiation models viewFactor and FVDOM. In his case, the software OpenFOAM ® was used and one of its applications in the evaluation of net rate heat exchanges by radiation on the mat of a real continuous furnace. The geometry, operational conditions, mesh definition, initial and boundary conditions used in the model were obtained from literature data, technical manuals and operational furnaces found in food industries. The implementation and simulation of physical model, in the OpenFOAM ® has several simplifying hypothesis highlighting air is treated as an ideal and incompressible, Newtonian and non-participant to the exchanges of heat by radiation; laminar flow viewFactor and FVDOM radiation models; pressure-velocity coupling algorithm SIMPLE. The results obtained were used to validate the radiation models through analytical results and also the convective heat flux. The orders of magnitude between radiation and convection turn it difficult to correctly evaluate the heat flux. Small fluctuations in temperature and velocity affect considerably and induce oscillations on the heat flux results. The viewFactor radiation model was more advantageous due to its greater simplicity and higher convergence velocity.
Validación numérica de los modelos de radiación viewfactor y FVDOM en lo openfoam ® y aplicación en lo estudio de los hornos alimenticios
Keywords: Food furnace; OpenFOAM ®; Radiation model